Regulation of Telecommunications: The Choice Between Market and Regulatory Failures (Journal of Law and Regulation, 2018)
Purpose ”“ The paper examines the main regulatory frameworks of the telecommunications industry through the concept of market failure and analyses how and why the policy often leads to undesirable outcomes that might be considered as regulatory failure.Methodology/approach/design ”“ The research uses the EU regulatory framework for electronic communications as a base for the analysis of the main policy objectives through the prism of the market failure theory with an eye to the interests of the main market players in the telecommunications markets.Findings ”“ About any aspect of regulation allows to find ways to create opportunities for some groups of the industry and stifle activity of others. Despite the theory of market failure provides reasonable justifications for regulation of telecommunications markets, it is possible to argue that many of these problems are mainly the consequence of the policy and could be better solved by market mechanisms.Originality/value ”“ The results of the research allow to look at the problems of telecommunications development and issues of the high level of concentration of the telecommunications markets as regulatory formed problems rather than consequences of the inherited industry’s characteristics.